The risk implications of diversification: Integrating the effects of product and geographic diversification - Mammen, Jan; Alessandri, Todd M.; Weiss, Martin (Long Range Planning, 2019)
The risk implications of product diversification have received considerable attention from scholars. However, our understanding of the effects of geographic diversification on risk is more limited. Relying on resource-based theory to frame our arguments, we argue that despite some similarities, the two types of diversification have differing effects on firm risk. We first establish the risk reducing effects for product diversification. We then integrate the unique aspects of geographic diversification that serve as a boundary condition to the RBV perspective, arguing for the risk increasing effects of geographic diversification. Finally, since many firms pursue both forms of diversification simultaneously, we explore the joint effects of both product and geographic diversification. We test our hypotheses in a longitudinal model on a sample of S&P 500 firms. Our findings suggest that total product diversification, as well as related diversification reduce risk, while total geographic diversification increases risk. Furthermore, our data provide evidence of a complex combination of joint effects of these two forms of diversification. These findings offer a more complete understanding of the risk effects of corporate diversification.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Firm risk; Geographic diversification; Product diversification; Resource-based view